TAKAFUL INSURANCE: A STUDY OF ISLAMIC FINANCE PRINCIPLES IN ACTION (Proceedings of International Conference on Scientific Research in Natural and Social Sciences, 2024)
This thesis investigates the framework and implications of takaful insurance, a distinctive model of cooperative risk management that aligns with Islamic principles. As an alternative to conventional insurance, takaful emphasizes mutual support and shared responsibility among participants, thereby fostering a community-oriented approach to financial protection. This research delves into the core principles of takaful, including the prohibition of riba (interest) and gharar (uncertainty), and examines how these principles shape its operational structure. The thesis categorizes various types of takaful, such as family and general takaful, and analyzes their respective roles in addressing the diverse needs of individuals and businesses within the context of ethical finance. Through a comprehensive review of regulatory frameworks and the influence of Sharia governance, the study highlights the challenges and opportunities facing takaful in both emerging and established markets. By evaluating its potential as a sustainable and equitable alternative to conventional insurance, this research aims to contribute to a deeper understanding of takaful's role in promoting social welfare and financial inclusion in the global economy.